Enhancing Intrinsic Work Motivation Through Work-Life Balance and Quality of Work Life: The Mediating Role of Work Engagement - ramandani, ummi salmah; Pareke, Fahrudin J.S (Universitas Muhammadiyah Pontianak, 2025)
This study examines the influence of work-life balance (WLB) and quality of work life (QWL) on intrinsic work motivation (IWM), with work engagement (WE) as a mediating variable. WLB and QWL are independent variables, while IWM is the dependent variable. A quantitative research design was employed using an online questionnaire distributed via Google Forms. The sample comprised 250 employees from five state-owned enterprises (Bank Mandiri, PT Telkom, BULOG, PT PLN, and PT Taspen) in Bengkulu City, Indonesia. Data were analyzed using SPSS 30 and SmartPLS 4, applying partial least squares structural equation modeling (PLS-SEM). The findings indicate that WLB and QWL positively and significantly affect IWM. Furthermore, work engagement effectively mediates the relationship between QWL and IWM but does not significantly mediate the relationship between WLB and IWM. The results underscore the importance of implementing WLB and QWL practices to foster intrinsic motivation among employees. This, in turn, enhances work engagement, productivity, and overall organizational efficiency, contributing positively to employee well-being and economic development.This study contributes to the human resource management (HRM) literature by highlighting work engagement as a key mediating mechanism between QWL and intrinsic motivation, particularly within the context of public sector organizations in Indonesia, which remains underexplored in existing research.